Observation of multi-mode: Upconversion, downshifting and quantum-cutting emission in Tm3+/Yb3+ co-doped Y2O3 phosphor - Yadav R.; Singh S.K.; Verma R.K.; Rai S.B. (My University, 2025)
Micro-crystalline Y2O3 phosphor co-doped with Yb 3+/Tm3+ has been synthesized and characterized. The phosphor material gives efficient multimodal emission via downshifting (DS), upconversion (UC), and downconversion (DC)/quantum cutting (QC) luminescence processes. Cross relaxation and co-operative energy transfer (CET) have been ascribed as the possible mechanism for QC; as result of which a UV/blue photon absorbed by Tm3+ splits into two near infrared photons (wavelength range 950-1050 nm) emitted by Yb3+. The Yb3+ concentration dependent ET efficiency and QC efficiency has also been evaluated. Such multi-mode emitting phosphors could have potential applications in increasing the conversion efficiency of solar cells via spectral modification. © 2014 Elsevier B.V. All rights reserved.